AN ANALYSIS OF MODALITY IN STUDENTS’ HORTATORY EXPOSITION TEXTS (SYSTEMIC FUNCTIONAL GRAMMAR PERSPECTIVE) - Ardiansah, Dian (Jurnal Pendidikan Bahasa dan Sastra, 2015)
AbstractThis study deals with the interpersonal meaning revealed the use of modality system in students’ hortatory exposition text at one of universities in Ciamis. Five texts of students’ hortatory exposition were analyzed to find out what types of modality are used and what interpersonal meaning which is contained through modality system. This study employed Systemic Functional Grammar (SFG) based on Halliday and Matthiessen’s (2004) framework since it can seek and identify the level of language structured which makes kinds of meaning.The findings showed that all of clauses which contained modality system indicated author’s interpersonal meaning with different value of language in the texts. The different types of language value and polarity also indicated the author’s interpersonal meaning in the texts. In addition, this analysis concluded that five texts comparised several modalization and modulation types which appeared with different ranks. Keywords: Hortatory exposition text, interpersonal meaning, SFG, modality AbstrakPenelitian ini berkenaan dengan makna interpersonal yang terungkap dari penggunaan sistem modalitas dalam teks eksposisi hortatory mahasiswa di salah satu universitas di Ciamis. Lima teks eksposisi hortatory mahasiswa dianalisis untuk mengetahui apa jenis modalitas yang digunakan dan apa makna interpersonal yang terkandung melalui sistem modalitas. Penelitian ini menggunakan Grammar Fungsional Sistemik (SFG) berdasarkan kerangka Halliday dan Matthiessen (2004) karena kerangka tersebut dapat mengidentifikasi tingkat bahasa terstruktur yang membuat berbagai jenis makna. Temuan penelitian ini menunjukkan bahwa semua klausa yang berisi sistem modalitas mengandung makna interpersonal penulis dengan nilai bahasa dalam teks yang berbeda. Berbagai jenis nilai bahasa dan polaritas juga menunjukkan makna interpersonal penulis dalam teks. Selain itu, penelitian ini menyimpulkan bahwa kelima teks memiliki beberapa tipe modalization dan modulasi yang muncul dengan peringkat yang berlainan.Kata kunci: Hortatory exposition text, makna interpersonal, modalitas, SFG,